Cardiac Shock Wave Therapy Ameliorates Myocardial Ischemia in Patients With Chronic Refractory Angina Pectoris: A Randomized Trial - Weijing, Liu; Ximin, Fan; Jianying, Shen; Mengyun, Zhu; Xuehua, Fan; Yawei, Xu; Liqiong, Hong (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac shock wave therapy (CSWT) is a non-invasive new option for the treatment of chronic refractory angina pectoris (CRAP). This study aimed to evaluate the safety and efficiency of CSWT in the treatment of CRAP. Methods: Eighty-seven patients with CRAP were randomly allocated into CWST group (n = 46) and Control group (n = 41). Canadian Cardiovascular Society (CCS) grade of angina pectoris, Seattle Angina Questionnaire (SAQ) score, 6-min walk test (6MWT), weekly dosage of nitroglycerin, and myocardial perfusion on D-SPECT were determined at baseline and during the follow-up period. Adverse events were also evaluated. Results: CSWT was well-tolerated in the CSWT patients. CSWT significantly improved the CCS grade, SAQ score, and 6MWT (p < 0.05). Imaging examinations showed that the ischemic area was reduced after CSWT. However, no significant changes were observed in the Control group. Conclusions: CSWT may improve the myocardial perfusion and reduce clinical symptoms without increasing adverse effects in CRAP patients. It provides a non-invasive and safe clinical therapy for CRAP patients. Clinical Trial registration:www.ClinicalTrials.gov, identifier: NCT03398096.